Dichotomaria marginata (Rhodophyta) as a bioindicator for marine pollution: An overview about its metabolites and adsorbed pollutants (Revista de Biología Marina y Oceanografía, 2020)
Macroalgae are considered bioindicators for marine pollution, because they have the ability to quickly react to changes in their environment. In consequence, macroalgae populations fluctuate, according to species characteristics and adaptive strategies. Their cell wall polysaccharides contain sulfate groups that are capable of retaining and accumulating heavy metals. In addition to traditional contaminants, emerging pollutants are being recognized in aquatic environments. Herein, emerging pollutants have been identified after being desorbed from the macroalga Dichotomaria marginata, collected from Fortaleza Beach, Ubatuba -SP, Brazil. Based on that algal polysaccharide networks have the potential of forming hydrogen bonds with polar compounds, it was hypothesized that these pollutants would be bound to sugar polymers. Compounds present in the D. marginata samples were identified using both gas and liquid chromatography/mass spectrometry (GC/MS and HPLC/MS), assisted by computational methods. It was possible to unequivocally identify 22 emerging contaminants with GC/MS, and 16 substances with HPLC/MS.